2017
DOI: 10.18203/issn.2454-5929.ijohns20174348
|View full text |Cite
|
Sign up to set email alerts
|

A large sinonasal schwannoma: a rare entity

Abstract: <p class="keywords"><span lang="EN-IN">Schwannoma is a rare neoplasm of nose and PNS which develops from Schwann’s cells of neural sheath and most are benign and encapsulated and amenable to surgical excision. The aim of this write-up is to report a rare case of schwannoma of nose and PNS. We report a case of 40 year old female, a housewife, presented in ENT OPD with complaints of nasal obstruction on right side, post nasal drip and headache. On diagnostic nasal endoscopy, there was a polypoidal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Schwannomas are benign nerve sheath tumors arising from the Schwann cells in the peripheral nerve sheath that are derived from the neuroectoderm, first described by Verocay in 1908. In the year 1935, Stout coined the term Neurilemmoma believing that this tumor arose from cells of sheath of Schwann 5 . Since these tumors are schwannian in origin, it is suggested that the term schwannoma be used more freuquently.…”
Section: Discussionmentioning
confidence: 99%
“…Schwannomas are benign nerve sheath tumors arising from the Schwann cells in the peripheral nerve sheath that are derived from the neuroectoderm, first described by Verocay in 1908. In the year 1935, Stout coined the term Neurilemmoma believing that this tumor arose from cells of sheath of Schwann 5 . Since these tumors are schwannian in origin, it is suggested that the term schwannoma be used more freuquently.…”
Section: Discussionmentioning
confidence: 99%
“…Mitra B et al [2] , Vaidya MM et al [3] , Dhawle MS et al [4] and Mangubat EZ et al [6] documented schwannoma in male patient. On the contrary, Singh M et al [5] , Mosalleum EMA [7] and Wong E et al [8] reported the lesion in female patients in their case reports.…”
Section: Discussionmentioning
confidence: 92%
“…Vaidya MM et al [3] , Dhawle MS et al [4] , Mangubat EZ et al [6] , Mosalleum EMA [7] et al documented the tumor in fourth decade. Singh M et al [5] observed the lesion in fifth decade.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations